Smoking behaviour of high school students in Manila - Mejillano, Evelina A. (Education quarterly.)
This study aims to determine the smoking behaviour of high school students in Manila. The respondents of this study were 1,508 third and fourth year students enrolled during the school year 1981-82 in the public high schools of the four districts of Manila. A study on anti-smoking promotes a great sense of anticipation for a generation of non-smokers.